2011
DOI: 10.1007/s11164-011-0241-y
|View full text |Cite
|
Sign up to set email alerts
|

Soft template synthesis of ZnO nanorods and their optical properties

Abstract: A simple solution route was developed to fabricate monodisperse wurtzite ZnO nanorods. The as-prepared samples were 5 lm in length and 70-100 nm in diameter. The crystallinity, morphology, and structure of the rod-like ZnO microcrystals were examined. The crystal phases and the microstructure of the nanorods were studied by X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). Room-and low-temperature photoluminescence (PL) and Raman spectra were employed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…As observed by SEM image, the average diameter of the ZnO nanorods increases with increased temperature (a) 70 (b) 80 FIGURE 11 | FESEM images of Aligned ZnO nanorods (Park et al, 2004). (Bhat, 2008); SEM image of Seed layer (B) and ZnO nanorods (C) (Yu et al, 2009); (D) SEM image of ZnO nanorods formed (Li et al, 2011). experience an increase in conductivity.…”
Section: Sensing Applicationsmentioning
confidence: 94%
See 2 more Smart Citations
“…As observed by SEM image, the average diameter of the ZnO nanorods increases with increased temperature (a) 70 (b) 80 FIGURE 11 | FESEM images of Aligned ZnO nanorods (Park et al, 2004). (Bhat, 2008); SEM image of Seed layer (B) and ZnO nanorods (C) (Yu et al, 2009); (D) SEM image of ZnO nanorods formed (Li et al, 2011). experience an increase in conductivity.…”
Section: Sensing Applicationsmentioning
confidence: 94%
“…The difficulty can be observed in growth on the substrate as the substrate has to be placed in the bottom of solution container for growth to occur (Amakali et al, 2020;Babar et al, 2020). Li et al (Li et al, 2011) reported a synthesis method that yields ZnO nanorod growth in the solution of 2 mM zinc acetate dodecyl benzene sulfuric acid sodium salt (DBS), dimethyl benzene, and hydrazine monohydrate (diluted by ethanol) stirred for 1 h, then boiled, and then refluxed for 5 h. The precipitates are filtered, washed, and dried (at 70°C in air), as shown in Figure 10D.…”
Section: Sol-gel Reflux Methodsmentioning
confidence: 99%
See 1 more Smart Citation